Physiological Blood of Baung Fish (Hemibagrus nemurus Blkr.) - Fitria, Nelmi; Tjong, Djong Hon; Zakaria, Indra Junaidi (Metamorfosa: Journal of Biological Sciences, 2019)
This study aimed  to examinine the physiological condition of Baung's blood ( Hemibagrus nemurus Blkr.) on the Batang Ombilin River, West Sumatra. This research uses quantitative descriptive method where quantitative data in the form of physic value is presented through comparison table average. The results showed the physiology of blood of Baung fish ( H. nemurus Blkr.) where the average amount of erythrocytes was similar in both sites where in Ombilin, the erythrocyte count had an average value of 2,268 x 10 6 cells/mm 3 and in Sawahlunto 2,267 x10 6 cell/mm 3 . While for the average number of leukocytes of Baung fish (H nemurus Blkr.) In Sawahlunto is greater than the average number of fish leukocytes in Ombilin where in Sawahlunto with an average leukocyte count of 3,5x10 4 cells / mm 3 and in Ombilin is 2,7x10 4 cells/mm 3 . And the blood hematocrit value of Baung fish. In Ombilin obtained a value of 38,8% and in Sawahlunto of 38,6%. As for the calculation of hemoglobin levels in both sites, hemoglobin levels were found in low levels of 8,5 g/dl in Ombilin and 5,4 g/dl in Sawahlunto. The levels of erythrocytes, leukocytes and blood hematocrit of Baung fish are at normal ranges. While hemoglobin levels at both sites were under normal conditions.